Cryptosporidiosis as a zoonotic disease, a review - Ramírez-Navarro, Viviana; Lopera-Vásquez, Ricaurte; Rodríguez-Gutiérrez, Victoria (Agronomía Mesoamericana, 2023)
Introduction. Cryptosporidium spp. is a protozoan parasite belonging to the group of coccidia, causing diarrhea, gastroenteric, and respiratory disorders (less frequently) in different vertebrate species worldwide, primarily in young individuals. Objective. To document the most important virulence and pathogenic characteristics of Cryptosporidium spp., as well as the description of its genetic variants and its zoonotic potential. Development. There are more of 19 species of Cryptosporidium spp., with C. parvum (humans), C. bovis (cattle), C. suis (swine), and C. ubiquitum (birds) being noteworthy due to their high infectivity capacity, given by the diversity of their virulence factors. The parasite has an affinity for enterocytes and causes abnormalities in the intestinal absorption and secretory functions. Cryptosporidiosis varies depending on the host’s status (age, nutrition, and immunity), the source of contamination (water or ingestion), transmission, and hygiene. Diagnostic techniques range from conventional coproscopic tests to molecular biology tests. Conclusion. Factors such as the variability and virulence factors of Cryptosporidium spp. are considered mechanisms that favor the infection and spread of the parasite at an individual and group level in humans and domestic animals, as well as the complexity of its life cycle, resistance to environmental conditions, the infective capacity, and host interaction consolidate Cryptosporidium spp. as a zoonotic agent with significant economic effects.